2013
DOI: 10.3390/ijms141121899
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticle-Based Calix[n]arenes and Calix-Resorcinarenes as Building Blocks: Synthesis, Formulation and Characterization

Abstract: Solid lipid nanoparticles (SLNs) have attracted increasing attention during recent years. This paper presents an overview about the use of calix[n]arenes and calix-resorcinarenes in the formulation of SLNs. Because of their specific inclusion capability both in the intraparticle spaces and in the host cavities as well as their capacity for functionalization, these colloidal nanostructures represent excellent tools for the encapsulation of different active pharmaceutical ingredients (APIs) in the area of drug t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 119 publications
1
23
0
1
Order By: Relevance
“…As crystallinity of NLC formulations increased, melting point increased as well. It is known that higher crystallinity (highly ordered lipid structure) affects negatively the performance of lipid based carriers such as less encapsulation efficiency and initial burst release in vitro [15]. However, in this study, interestingly NLC/HTCC_I formulation showed relatively high crystallinity compared to the other formulations, which seems not to affect the encapsulation efficiency and in vitro drug release.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 38%
See 1 more Smart Citation
“…As crystallinity of NLC formulations increased, melting point increased as well. It is known that higher crystallinity (highly ordered lipid structure) affects negatively the performance of lipid based carriers such as less encapsulation efficiency and initial burst release in vitro [15]. However, in this study, interestingly NLC/HTCC_I formulation showed relatively high crystallinity compared to the other formulations, which seems not to affect the encapsulation efficiency and in vitro drug release.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 38%
“…Melting peak did not appear in NLC/HTCC_I formulation, but tiny peaks were observed in NLC_I (116.9˝C) and NLC/CS_I (114.4˝C) formulations. carriers such as less encapsulation efficiency and initial burst release in vitro [15]. However, in this study, interestingly NLC/HTCC_I formulation showed relatively high crystallinity compared to the other formulations, which seems not to affect the encapsulation efficiency and in vitro drug release.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 55%
“…This size regime has rarely been obtained using related macrocyclic amphiphiles, which generally produce larger than 100 nm solid lipid nanoparticles. 22 The size and size distribution of the particles can be decreased by using dilute calixpyrrole suspension and smaller ethanol concentration. The ζ-potential measurements showed that the particles were stabilized by a negative surface charge even at neutral and slightly acidic pH.…”
Section: Discussionmentioning
confidence: 99%
“…21 Regarding the use of novel amphiphiles as molecular building blocks, it is important to elucidate how structural factors of the amphiphiles in conjunction with the preparation parameters affect the structure and stability of the nanoparticles. 22 In the present work, resorcinol-extended meso-dodecyl calixpyrrole 1 was found to spontaneously aggregate into very small and stable nanoparticles without mechanical processing, such as sonication. …”
Section: Introductionmentioning
confidence: 99%
“…7 In addition to the conventional lipids used for producing this type of carriers, a new class of the SLNs based on self-assembled amphiphilic calix [4]arenes was developed by P. Shahgaldian and A. Coleman et al 8 Functionalization of both an upper and a lower rims of the p-tert-butylcalix [4]arene by hydrophilic and hydrophobic fragments is a common approach (Scheme 1) to obtain such amphiphilic molecules. [12][13][14] We suggest alternative way based on our previous study 15 consisting of stepwise functionalization of the lower rim of p-tert-butylthiacalix [4]arene platform by hydrophilic and hydrophobic moieties, spatial separation of which is provided by using 1,3-alternate conformation of the molecular platform (Scheme 1). For p-tertbutylthiacalix [4]arene the bond length between the aromatic residue and bridging group is 15% larger than the one in methylene bridged p-tert-butylcalix [4]arene, 16,17 that provides weaker circular hydrogen bond and as a result greater conformational flexibility of the molecular platform that makes p-tert-butylthiacalix [4]arene an ideal candidate for design such amphiphilic molecules.…”
Section: Introductionmentioning
confidence: 99%